2022
DOI: 10.15835/nbha50212639
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of essential oil and hydrolate from a new hyssop variety (Hyssopus officinalis L.)

Abstract: The main objective of this study was to evaluate the quality of essential oil (EO) and hydrolate (HY) obtained from a new Romanian variety of hyssop (Hyssopus officinalis L., Lamiaceae family), namely ‘Cătălin’. The chemical composition and the concentration of the compounds was established by gas chromatography coupled to mass spectrometry (GC/MS). The main constituents identified in hyssop EO and HY were cis-pinocamphone (34.63% and 67.00%), trans-pinocamphone (11.72% and 14.58%), thujenol (1.39% and 6.05%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The minor constituents such as 1,8-cineole might be involved in the antibacterial activity of hydrolates [ 25 ]. The antimicrobial activity of thujone has also been confirmed [ 35 , 36 , 37 ]. Some researchers suggested that the hydroxyl groups of eugenol could bind to proteins by preventing the action of microbial enzymes [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The minor constituents such as 1,8-cineole might be involved in the antibacterial activity of hydrolates [ 25 ]. The antimicrobial activity of thujone has also been confirmed [ 35 , 36 , 37 ]. Some researchers suggested that the hydroxyl groups of eugenol could bind to proteins by preventing the action of microbial enzymes [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies addressing the antioxidant properties of hydrolates. Their results show moderate to very low antioxidant capacity [ 37 , 46 ]. These results are consistent with the results of our study (see Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation